Oxidative stress in COPD - MacNee, William (Henry Stewart Talks, 2012)
The involvement of oxidative stress in the pathogenic mechanisms of COPD, Downregulation of antioxidant defenses, Enhanced inflammation, Apoptosis, Protease/antiprotease imbalance, Accelerated aging, Immunemodulation, Potential for targeted therapy
Archived at 2021/02/25